Antioedematous and Analgesic Properties of Fertile Fronds of Drynaria quercifolia. (20th January 2014) - Anuja, G. I.; Latha, P. G.; Shine, V. J.; Suja, S. R.; Shikha, P.; Satheesh Kumar, K.; Rajasekharan, S.
Abstract : Inflammation is a complex biological response of tissue cells to harmful stimuli including trauma, tissue necrosis, and infections which plays a key role in the pathophysiology of many deadly diseases. In ethnomedicine Drynaria quercifolia fronds are used to treat inflammation as poultice on swellings and as antibacterial, hepatoprotective, and antipyretic agent. Herein, we have evaluated the antioedematous, antiproliferative, and analgesic properties of the ethanolic extract of fertile fronds of D. quercifolia (FF) by standard procedures. Oral administration of FF produced significant inhibition of carrageenan and histamine induced paw oedema in Wistar rats. FF significantly reduced both wet weight and dry weight of granuloma tissue which shows the inhibitory effect on exudative and proliferative phases of inflammation. FF significantly attenuated acute and delayed phases of formalin induced pain, acetic acid-induced writhing, capsaicin-induced nociception, and hot plate test in mice. Phytochemical analysis revealed the presence of coumarins, flavonoids, glycosides, phenolics, saponins, steroids, tannins, and terpenoids. Total phenolic content was 186 mg/g equivalent of gallic acid. The HPLC estimation showed flavanone glycoside naringin (1.2%) and its aglycone naringenin (0.02%). The presence of potent anti-inflammatory and analgesic principles in FF and their synergistic action may be the reason for the proposed therapeutic effects.